Efficient Triplet–Triplet Annihilation Upconversion in an Electroluminescence Device with a Fluorescent Sensitizer and a Triplet‐Diffusion Singlet‐Blocking Layer. Issue 50 (11th October 2018) - Chen, Chia‐Hsun; Tierce, Nathan T.; Leung, Man‐kit; Chiu, Tien‐Lung; Lin, Chi‐Feng; Bardeen, Christopher J.; Lee, Jiun‐Haw
Abstract: Solid‐state triplet–triplet annihilation upconversion (TTAUC) blue emission in an electroluminescence device (i.e., an organic light‐emitting diode (OLED)) is demonstrated. A conventional green fluorophore, tris‐(8‐hydroxyquinoline)aluminum (Alq3 ), is employed as the sensitizer that generates 75% triplet under electrical pumping for the blue triplet–triplet annihilation emitter, 9, 10‐bis(2′‐naphthyl) anthracene (ADN), with the heterojunction bilayer structure. The operation lifetime is elongated both for ADN blue (4.1x) and Alq3 green (34.8%) emission due to efficient use of excitons and separation of recombination and emission zone. To reduce the singlet quenching (SQ) of blue TTAUC signal by the Alq3 sensitizer with lower bandgap, 1‐(2, 5‐dimethyl‐4‐(1‐pyrenyl)phenyl)pyrene (DMPPP) is inserted between the Alq3 and ADN as a triplet‐diffusion‐and‐singlet‐blocking layer. DMPPP exhibits triplet energy close to Alq3 and higher than ADN, as well as higher singlet energy than both Alq3 and ADN. It allows triplet diffusion from Alq3 to ADN, but blocks the SQ of the blue TTAUC signal by Alq3 . 86.1% intrinsic efficiency of TTAUC is demonstrated in this trilayer (Alq3 /DMPPP/ADN) OLED. Abstract : Efficient triplet–triplet annihilation upconversion (TTAUC) in an electroluminescence device with a fluorescent sensitizer is demonstrated. Under electrical pumping, 75% of the triplets are generated in the fluorophore, which can be used as the sensitizer for the TTAUC process by heterojunction trilayer structure. Operation lifetime increases and the overall conversion intrinsic efficiency of TTAUC reaches 86.1%.